VISUALIZATION AND COMPREHENSION: Corroborating children’s reading ability - Moriyanti Moriyanti; Hayatul Muna; Nyak Mutia Ismail (Universitas Islam Negeri Banda Aceh, 2019)
This study aimed at finding out the influence of visualization on students’ reading comprehension ability. Quantitative approach was employed in carrying out this research. The data were collected through test as it was the main instrument of this study. The data analysis was carried out using manual statistics calculation to find out the mean score before and after the treatment. From the result, it was obtained that the most effect that visualization has is on the inferring; second, it is on details; then it is followed by main idea. The smallest influence is made on vocabulary. Thus, it can be concluded that visualization while reading can help students a lot in terms of inferring, details, and main idea.